Endovascular treatment of the rupture of thoracic aortic aneurysm, manifested by a neurological «mask» - A. N. Ryazanov; V. V. Soroka; S. P. Nokhrin; D. V. Kandyba; S. A. Platonov; V. N. Zhigalo; A. V. Osipov; A. B. Kurilov; E. P. Ryazanova; P. M. Malkova (Вестник хирургии имени И.И. Грекова)
The article describes a case of successful treatment of the rupture of aortic aneurysm by the endovascular method. Patient P., 71 years old, was hospitalized in a multidisciplinary hospital with a diagnosis of acute cerebral circulation disorder. The patient was examined in the intensive care unit. Signs of neurological symptoms regressed. Spiral computed tomography of the chest organs was performed with suspected pulmonary embolism, the results of which revealed an aneurysm of the descending thoracic aorta, complicated by a rupture with the formation of a right-sided hemothorax. The patient underwent endoprosthesis of the thoracic aorta with stent graft. After 2 days, thoracoscopic sanitation, drainage of the right pleural cavity was performed. The postoperative period proceeded without peculiarities. The patient was discharged on the 12th day in satisfactory condition. At control examination in 1, 6, 12 months, the long-term steady positive result was noted. Endovascular methods minimize the risk of postoperative complications, contributing to a favorable outcome of the disease.